2016
DOI: 10.1097/j.pain.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-mediated mu-opioid receptor phosphorylation and desensitization in rats, and its prevention during early diabetes

Abstract: Painful diabetic neuropathy is associated with impaired opioid analgesia; however, the precise mechanism in sensory neurons remains unclear. This study aimed to identify putative mechanisms involved in modified opioid responsiveness during early streptozotocin-induced diabetes in rats. In this study, we demonstrate that in diabetic animals, impaired peripheral opioid analgesia is associated with a reduction in functional mu-opioid receptor (MOR) G protein coupling. Mu-opioid receptor immunoreactive neurons col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…However, NO formed from the dietary l-arginine, may have attenuated perineurial hypoxia and the associated oxidative stress, as well as reducing otherwise elevated levels of diacylglycerol and activated protein kinase C (PKC), that are produced as a consequence of persistent hyperglycaemia in diabetes. 14,15 Of particular importance to the present work, PKC mechanisms are implicated in desensitization of the opioid receptor [16][17][18][19][20][21][22] as well as the development of diabetic complications. 16 A role for PKC in the development of opioid hyposensitivity in diabetes is supported by observation that supraspinal pretreatment of STZ-diabetic rats with the PKC inhibitor, calphostin C, prevented the development of opioid hyposensitivity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, NO formed from the dietary l-arginine, may have attenuated perineurial hypoxia and the associated oxidative stress, as well as reducing otherwise elevated levels of diacylglycerol and activated protein kinase C (PKC), that are produced as a consequence of persistent hyperglycaemia in diabetes. 14,15 Of particular importance to the present work, PKC mechanisms are implicated in desensitization of the opioid receptor [16][17][18][19][20][21][22] as well as the development of diabetic complications. 16 A role for PKC in the development of opioid hyposensitivity in diabetes is supported by observation that supraspinal pretreatment of STZ-diabetic rats with the PKC inhibitor, calphostin C, prevented the development of opioid hyposensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…14,15 Of particular importance to the present work, PKC mechanisms are implicated in desensitization of the opioid receptor [16][17][18][19][20][21][22] as well as the development of diabetic complications. 16 A role for PKC in the development of opioid hyposensitivity in diabetes is supported by observation that supraspinal pretreatment of STZ-diabetic rats with the PKC inhibitor, calphostin C, prevented the development of opioid hyposensitivity. 23,24 In recent work by others in STZ-diabetic rats exhibiting opioid hyposensitivity, MOP receptor immunoreactive primary sensory neurons were co-localized with activated PKC isoforms as well as with the receptor for advanced glycation end products (RAGE).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are 12 known isoforms of PKC, which are further categorized into three subgroups according to their structure and mechanisms of activation. A recent study has shown that the expression of PKCα and PKCε is increased in the spinal cord of diabetic animals; however, the expression of PKCβ or PKCγ was not altered (Mousa et al, 2016), suggesting subtype specific PKC isoforms are involved in diabetic neuropathy. Thus, future work might be necessary to evaluate the role of specific PKC isoforms in the RVM in modulating neuropathic pain induced by type 2 diabetes.…”
Section: Discussionmentioning
confidence: 94%